(untitled) (Journal of the Society for Musicology in Ireland, 2021)
A review of Carina Drury, Irlandiani: Carina Drury, Eimear McGeown, Nathaniel Mander, Aileen Henry, Poppy Walshaw, Penny Fiddle Records (2020), (CD and Digital Album) PFR2005CD.